2020
DOI: 10.1002/cbdv.202000043
|View full text |Cite
|
Sign up to set email alerts
|

Two Phytotoxins Isolated from the Pathogenic Fungus of the Invasive Weed Xanthium italicum

Abstract: Alternariol and altenuisol were isolated as the major phytotoxins produced by an Alternaria sp. pathogenic fungus of the invasive weed Xanthium italicum. Altenuisol exhibited stronger phytotoxic effect compared with alternariol. At 10 μg/mL, alternariol and altenuisol promoted root growth of the monocot plant Pennisetum alopecuroides by 11.1 % and 75.2 %, respectively, however, inhibitory activity was triggered by the increase of concentration, with root elongation being suppressed by 35.5 % and 52.0 % with al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 25 publications
(26 reference statements)
0
13
0
Order By: Relevance
“…Both alternariol (18) and alternuisol (22) were isolated from the cultures of Alternaria sp., the pathogen of the invasive weed Xanthium italicum. They inhibited shoot and root growth of Pennisetum alopecuroides and Medicago sativa by seedling growth assay [43]. Further stud-ies on the mode of action showed that alternariol (18) and alternariol-9-methyl ether (also called AME, 19) from Alternaria alternata inhibited the photosynthetic electron transport chain in isolated spinach chloroplasts [44].…”
Section: Dibenzopyronesmentioning
confidence: 99%
See 2 more Smart Citations
“…Both alternariol (18) and alternuisol (22) were isolated from the cultures of Alternaria sp., the pathogen of the invasive weed Xanthium italicum. They inhibited shoot and root growth of Pennisetum alopecuroides and Medicago sativa by seedling growth assay [43]. Further stud-ies on the mode of action showed that alternariol (18) and alternariol-9-methyl ether (also called AME, 19) from Alternaria alternata inhibited the photosynthetic electron transport chain in isolated spinach chloroplasts [44].…”
Section: Dibenzopyronesmentioning
confidence: 99%
“…Agropyrenal (43), a naphthol, was isolated from the liquid cultures of Ascochyta agropyrina var. nana.…”
Section: Naphthalene Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…The biological invasion has become a great challenge for human beings. Xanthium italicum Moretti is one of the most widely distributed invasive plants in the world, and its biological characteristics of easily carrying seeds make it more likely to spread widely 6 . X. italicum is an annual herbaceous plant of the genus Xanthium in the Compositae family, propagated by seeds 7 , and native to North America but has been spread to many countries and regions in Europe, Asia, and Oceania 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that the phenolic hydroxyl group played a key role in the toxicity to soybean cell culture [183]. AOH inhibited root growth of Pennisetum alopecuroides, Medicago sativa, and Amaranthus retroflexus at 1000 µg•mL −1 [184]. AME inhibited the electron transport chain of spinach chloroplasts with an IC 50 value of 29.1 µM, and inhibited the growth of Synechococcus by directly interacting with one or more of the electron carriers involved in the electron transport chain [185].…”
Section: Dibenzopyranonesmentioning
confidence: 99%